Isotope Effect in D2O Negative Ion Formation in Electron Transfer Experiments - Kumar, Sarvesh (2023)
This work was also supported by the Radiation Biology and Biophysics Doctoral Training Programme (RaBBiT, PD/00193/2012). P.L.-V. also acknowledges his visiting professor position at Sophia University. The computations were enabled by resources provided by the Swedish National Infrastructure for Computing (SNIC) at Chalmers Centre for Computational Science and Engineering (C3SE) and partially funded by the Swedish Research Council through Grant Agreement 2020-05293. G.G. acknowledges partial financial support from the Spanish Ministerio de Ciencia e Innovación (Project PID2019-104727RB-C21), Ministerio de Universidades (Project PRX21/00340), and CSIC (Project LINKA20085). The work is part of COST Action CA18212 - Molecular Dynamics in the GAS phase (MD-GAS). Publisher Copyright: © 2023 The Authors. Published by American Chemical Society.